2016
DOI: 10.1002/macp.201600076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optoelectronic Properties of Benzo[1,2‐b:4,5‐b′]dithiophene‐Based Copolymers with Conjugated 2‐(2‐Ethylhexyl)‐3,4‐dimethoxythiophene Side Chains

Abstract: In order to regulate the electronic ability of benzo [1,2-b:4,5-b′]dithiophene (BDT), the new electron-donating unit (BDTOT) is designed and synthesized which consists of a BDT backbone with conjugated 2-(2-ethylhexyl)-3,4-dimethoxythiophene side chains. By alternating copolymerization of BDTOT with electron-accepting units of fluorinated benzothiadiazole (FBT), benzothiadiazole (BT), and pyrrolo[3,4-c]pyrrole-1,4-dione (DPP), three donor-acceptor (D-A) copolymers (PBDTOT-FBT, PBDTOT-BT, and PBDTOT-DPP) have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This complexity limits and challenges the understanding of the role of each material in the optoelectronic phenomenon and thus their development. Similar approaches have been addressed using ternary mixtures within bulk-heterojunction OPVs including the use of copolymers synthesized by the combination of electron-deficient and electron-rich comonomers, so-called push–pull or donor–acceptor polymers, through relatively difficult synthetic processes. The bulk-heterojunction architecture also often leads to an increased complexity of engineering the OPV systems due to the nanophase morphology. This inhibits understanding and decouples the relationship between the molecular structure of each material and the morphology of the active layer on the optics, charge transport, and performance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…This complexity limits and challenges the understanding of the role of each material in the optoelectronic phenomenon and thus their development. Similar approaches have been addressed using ternary mixtures within bulk-heterojunction OPVs including the use of copolymers synthesized by the combination of electron-deficient and electron-rich comonomers, so-called push–pull or donor–acceptor polymers, through relatively difficult synthetic processes. The bulk-heterojunction architecture also often leads to an increased complexity of engineering the OPV systems due to the nanophase morphology. This inhibits understanding and decouples the relationship between the molecular structure of each material and the morphology of the active layer on the optics, charge transport, and performance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the PBDTDPPcbp: PCBM based OSC, the substitution of 11-ethyltricosane increases the miscibility of PDPPBDT, thereby the J sc (7.12 mA/cm 2 ) and FF (62%) in PDPPBDT: PC 71 BM based OSC both enhanced, which further proves the above-conclusions. Subsequently, based on the alkyl chain substituted PPD unit, PQ3 (2015) was reported by Liu et al [136] ; PBDTBA(H)-DPP (2015) andPBDTBPA(F)-DPP (2015) were prepared by Chakravarthi et al [147] ; PBDTS-DPP (2016) ,PBDTOT-DPP (2016) and P2 (2016) were synthesized by Zhang et al [73] , Wang et al [148] and Kranthiraja et al [139] , respectively. Similarly,PBDTT-S-DPP (2016) , [149] PBDTT-Se-DPP (2016) , [149] P3 (2016) , [150] P7(0.0: 1.0) (2016) , [151] PDPP-BDT (2021) [152] and PDPP-BDT-Cl (2021) [152] were also prepared in subsequence.…”
Section: δ-π-α-π τψπε πολψμερ δονορςmentioning
confidence: 99%
“…Subsequently, considering further enhancing the electronegativity of acceptor unit in the main-chain engineering is an effective molecular design strategy, Shen et al [163] and Liu et al [136] based on the polymer backbone BDT-TR-BTDz-TR, reported PBTFBT (2013) and PB4 (2015) by introducing two "F" atoms into the BTDz unit. Afterward, PBDT2FBT-Th (2015) , [273] PBDT2FBT-Ph (2015) , [273] PBDTS-DTFBT (2016) , [73] PBDTOT-FBT (2016) , [73] PBDTOT-BT (2016) , [148] PBDTBP-DTffBT (2016) , [274] P1(1.0: 0.0) (2016) , [151] PBDT-DTBTff (2017) , [57] P3 (2017) , [268] PBDTEDOT-FBT (2018) , [269] PBDT-FBT (2018) , [275] PBDTF-FBT (2018) , [275] PBDTS-FBT (2018) , [275] PBDTSF-FBT (2018) [275] and PBTF (2018) [276] were also successfully synthesized. Among these donors, due to "F" atom with a strong electron-withdrawing optimizes the HOMO energy level of polymer donors as well as promotes the hole/electron mobility in corresponding OSCs.…”
Section: As For the Main-chain Engineering Bdt-t-bsdz-t Bdt-t-btz-t A...mentioning
confidence: 99%
“…A breakthrough with a PCE of 9.29% was made by Yang and coworkers in 2016, in which an unsubstituted BDT was used to construct the novel D–A polymer of PBDT-DTFFBT . Also, two-dimensional (2D) BDT polymers have been presented in recent years and have showed improved photovoltaic properties over those of 1D BDT polymers. Among these D–A polymers with a BDT unit, it is found that different acceptor units, such as ester-substituted thieno­[3,4- b ]­thiophene (TT), benzo­[ c ]­[1,2,5]­thiadiazole (BT), and benzo­[1,2- b :4,5- b ′]­dithiophene-4,8-dione (BDD) played an important role in improvement of photovoltaic performance. Therefore, it is very important to alternate donor and acceptor units for constructing high-performance D–A photovoltaic polymers.…”
Section: Introductionmentioning
confidence: 99%